THE ROLE OF ELECTRONIC HEALTHCARE SERVICES IN THE PREVENTION OF CARDIOVASCULAR DISEASES IN THE POPULATION (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Cardiovascular diseases remain the leading cause of morbidity and mortality worldwide, posing a significant burden on healthcare systems and public health. Effective prevention strategies are essential to reduce disease incidence, improve early detection, and enhance long-term disease management. In recent years, electronic healthcare services, including telemedicine, electronic medical records, mobile health applications, and remote patient monitoring, have emerged as important tools in cardiovascular disease prevention. This article aims to evaluate the role of electronic healthcare services in the prevention of cardiovascular diseases among the general population. Particular attention is given to the use of digital health technologies for risk assessment, early diagnosis, lifestyle modification, and continuous monitoring of cardiovascular risk factors. The study analyzes how electronic healthcare systems contribute to improved access to preventive care, patient engagement, and timely medical intervention. Understanding the potential of electronic healthcare services in cardiovascular disease prevention may support the development of more effective, accessible, and sustainable public health strategies.
Keywords: Cardiovascular diseases, electronic healthcare, e-health services, disease prevention, telemedicine, digital health, public health.